POSSIBLE FACTORS INFLUENCING THE WILLINGNESS TO USE ENGLISH IN TEACHING JAPANESE AS A FOREIGN LANGUAGE BY NON-NATIVE SPEAKERS - Luchenko, Olha; Doronina, Olha; Chervinko, Yevhen (Sustainable Multilingualism / Darnioji daugiakalbystė, 2024)
In recent years, teachers have had students from diverse language and cultural backgrounds in their classrooms due to increasing human migration in many countries. Therefore, multilingual learning and teaching have become a widespread phenomenon. Research on English language teaching and learning in multilingual contexts has gained great importance. However, teaching languages other than English and foreign language teachers’ practices in this specific context have received little attention so far. Teaching the highly contextualised Japanese language poses challenges in multilingual classrooms, and teachers more frequently resort to using English as the medium of instruction. To shed light on Japanese non-native teachers’ practices, the study explored and analysed two hundred and seventy-four teachers’ responses to the questionnaire “Teaching the Japanese language in multilingual classrooms – English medium instruction approach (EMI)”. The research attempts a worldwide study on using EMI in teaching Japanese as a foreign language (JFL). It examines a broad geographic scope of JFL teachers’ practices from fifty-seven predominantly non-Anglophone countries. The present article focuses on investigating various factors affecting JFL teachers’ willingness to use EMI that can be classified into demographic, linguistic, and contextual. The results revealed several factors of significant influence, such as JFL teachers’ work experience, the highest education level attained, educational stage, geographic region, native language group, Japanese language proficiency, and knowledge of other languages (multilingualism). The factors that appeared to be of insufficient influence were age, study of teaching methods/linguodidactics and level of Japanese taught. The factor of JFL teachers’ language proficiency (both English and Japanese) falls into a separate category of influence, where a significant difference was noted for proficient and near-native levels.